Civil Law and Juridical Aspects in the Distribution of Marriage Joint Property - Sisca Ferawati Burhanuddin (Budapest International Research and Critics University, 2021)
In a marriage, there is a mechanism that must be borne by both parties if a divorce has occurred, including the distribution of joint property or what we often know as 'gono gini' assets. This study uses a descriptive method with a qualitative approach and data triangulation analysis, the results of the study explain that the distribution of joint property in marriage is decided based on the Constitution as the legal basis that regulates the mechanism of the divorce process, court decisions require husband and wife to divide their marital property equally. fair and unanimous, because in its stipulations Gono Gini property is an asset that is produced from marriage wealth, the law is absolutely joint property and is used for household purposes, so the conclusion is that the process of dividing joint assets resulting from marriage can be used jointly, but the innate property of each of the proceeds before the legal marriage becomes private property.